Stages and forms of development of Doctor Bormental network of clinics - A. V. Bobrovsky (Бюллетень сибирской медицины)
One of the marked tendencies in the last time is the development of medical networks. The experience of Doctor Bormental network of medical centers dealing with overweight therapy indicates that now this structure is optimal; it most efficiently combines the high-quality medical care for patients and the economic efficiency of medical business.